Sociology, Neoliberalism and the Emperor’s clothes - Castillo Rivadeneira, Oscar (2021)
The article describes the main characteristics of Neoliberalism and its effects on Social Sciences, with references to the key themes of that ideology. It also describes the way it became «common sense» in economic thinking and its effects on State management, public policies and precarious basic education and health services, among others. Thus, for almost three decades, Neoliberalism isolated Social Sciences, especially Sociology, because of a supposed «efficient pragmatism», revealing the individualism, the minimization of the State and the absolute law of the market in the reproduction of society.However, three decades later, and especially in 2020, in the context of the COVID-19 pandemic, all the fallacies of «Neoliberal Thought» have been demonstrated, creating new conditions for a return of Social Sciences, with the capacity to understand and to analyze the new social processes that have occurred in our society. The principles of ethics, solidarity and associativity start to be reassessed, especially in the popular classes, in a context of globalization and capitalist modernization.